Fetal cerebral hemorrhage due to X‐linked GATA1 gene mutation. (24th July 2018) - Bouchghoul, Hanane; Quelin, Chloé; Loget, Philippe; Encha‐Razavi, Féréchté; Senat, Marie‐Victoire; Maheut, Lorraine; Galimand, Julie; Collardeau‐Frachon, Sophie; Da Costa, Lydie; Martinovic, Jelena
Abstract: We report a multiplex family with a GATA1 gene mutation responsible for a massive fetal cerebral hemorrhage occurring at 36 weeks. Two other stillbirth cousins presented with fetal hydrops and congenital hemochromatosis' phenotype at 37 and 12 weeks of gestation. Molecular screening revealed the presence of a c.613G>A pathogenic allelic variation in exon 4 of GATA1 gene in the 3 male siblings and their carrier mothers. The diagnosis of a GATA1 gene mutation may be suspected in cases of male fetuses with intracerebral bleeding, particularly if a history of prior fetal loss(es) and mild maternal thrombocytopenia are also present. Abstract : What's already known about this topic? Fetal cerebral hemorrhage has been linked so far either to alloimmune thrombocytopenia, to clotting deficiency, or to COL4A1/A2 mutations. What does this study add? This study enlarges the spectrum of fetal anomalies associated to GATA1 gene mutations adding a new finding, ie, fetal intracranial bleeding.